Analisis Peran Dan Kinerja Account Officer Di Bidang Pembiayaan Pada Bank Syariah Indonesia (BSI) KCP. Jambi Gatot Subroto - Ayu Wandira; Agustina Mutia; Muhamad Subhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Banking is one way to solve problems related to business finance. Banking is a place to provide financing to develop a business that is being worked on. According to the theory, Account Officers have an important impact on determining customers. The formulation of the problem in this study is How is the analysis of the role of the Account Officer in overcoming problematic financing at the BSI KCP Gatot Subroto bank? and How is the performance analysis of the Account Officer in overcoming problematic financing at the BSI KCP Gatot Subroto bank? This study uses a qualitative research method with a type of field study research. Data was collected through interviews, documentation and observation. The results of this study mention the role of the account officer in analyzing and processing financing applications at the BSI KCP Ponorogo bank including managing accounts, managing products, managing financing and managing sales by approaching debtors and the need for review at any time. The performance of the BSI KCP Gatot Subroto bank account officer in preventing problematic financing at the BSI KCP Gatot Subroto bank includes the financing application stage where the account officer gives time to prospective debtors to complete the requirements as a standard selection in financing, the financing proposal stage with reference to the selection of information obtained from existing social, the stage of providing financing facilities which shows that the account officer offers existing facilities based on the features of the selected prospective debtor, the financing stage which reviews the financing facilities by reviewing the financing facilities obtained by the prospective debtor or debtor. The efforts to resolve problematic financing at BSI KCP Gatot Subroto bank are financing restructuring which includes rescheduling.